A statistical approach to the development of flame retardant and mechanically strong natural fibers biocomposites. (July 2022) - Pérez-Chávez, Ricardo; Sánchez-Aguilar, Jöns; Calderas, Fausto; Maddalena, Lorenza; Carosio, Federico; Sanchez-Olivares, Guadalupe
Highlights: A statistical approach is applied to the production of sustainable biocomposites Keratin fibers from industrial waste are employed to replace aluminum hydroxide The effects of combined compounding variables are thoroughly analyzed The optimal balance between flame retardant and mechanical properties is achieved Abstract: Flame retardant polymer composites are conventionally produced by extrusion processes where several compounding variables must be finely tuned in order to find the optimal balance between the needed flame retardant and mechanical properties. This work aims at the production of flame retardant and mechanically strong biocomposites based on thermoplastic starch, keratin fibers derived from tannery industry waste and aluminum trihydroxide by exploiting a statistical approach. The response surface methodology is applied to investigate the effects of compounding variables, aiming to minimize the total flaming time, maximize the tensile strength and reduce the aluminum trihydroxide content by replacing it with keratin fibers. The fiber length, blending temperature and rotational speed are found to produce fundamental interaction effects on the final properties of the flame retardant biocomposites. The applied statistical method is validated by the experimental results. The proposed approach can thus enable the production of sustainable biocomposites where sustainability, flame retardancy and mechanical properties are maximized.